The effects of heat treatment files and taper lock depth on the torsional fatigue resistance of rotary NiTi instruments - Haryanto, Viola Shelvannia; Stefani, Rosita; Eddy, Eddy; Iskandar, Bernard Ongkie (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: A file fracture is a significant complication in endodontic treatment, particularly when it obstructs access to the apical root canal. The primary cause is torsional fatigue, occurring when applied force exceeds the elastic limit of NiTi alloys. Heat-treated rotary files have been developed to improve torsional resistance. Objective: To compare the time to fracture due to torsional fatigue between gold and blue heat-treated rotary files under taper lock conditions. Methods: A total of 48 heat-treated rotary files (#25.04) were embedded in bulk-fill composite resin blocks to simulate taper lock. Samples were randomly divided into eight groups (n=6): E-Flex Gold (3 mm, 5 mm), EndoArt Smart Gold (3 mm, 5 mm), E-Flex Blue (3 mm, 5 mm), and EndoArt Smart Blue (3 mm, 5 mm). Torsional fatigue time was recorded from the start of rotation using an endomotor until fracture occurred. Results: One-way ANOVA revealed a statistically significant difference in torsional fatigue time among groups (p<0.05). Conclusion: Blue heat-treated rotary files showed longer fracture times and may be safer in high taper lock conditions, although results are limited by the in vitro resin model.